If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 10 = x + -11 Reorder the terms: 10 + 4x = x + -11 Reorder the terms: 10 + 4x = -11 + x Solving 10 + 4x = -11 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + 4x + -1x = -11 + x + -1x Combine like terms: 4x + -1x = 3x 10 + 3x = -11 + x + -1x Combine like terms: x + -1x = 0 10 + 3x = -11 + 0 10 + 3x = -11 Add '-10' to each side of the equation. 10 + -10 + 3x = -11 + -10 Combine like terms: 10 + -10 = 0 0 + 3x = -11 + -10 3x = -11 + -10 Combine like terms: -11 + -10 = -21 3x = -21 Divide each side by '3'. x = -7 Simplifying x = -7
| 4-(3x+1)=-3x+3 | | 2(8x-4)-2x=14x+12 | | x^2-9abx+20a^2b^2=0 | | -6x-4=14 | | 6b-12=-8 | | -4+6= | | 1.25k-3(.25k+6)=12 | | 3+r=2 | | 5w^2-3w=224 | | 4b+2(b-4)=8(b+3) | | -2(8-3)=6x+2 | | 5-.3t=.7t-.11 | | 4t^2-2t-6=0 | | 7x^2+11x+4=0 | | (5w+32)(w-7)=0 | | 4/5-x/5=-4/5 | | 6c+6y=24 | | 2u^2-6=u | | a^2b^2+14ab+49=0 | | 6a^2b+5ab-4b=0 | | 5s-9=2(5-6) | | 3(4a+1)=14a | | 2(x+3)=5x+2-3x | | 10a^2+5ab-15b^2=0 | | 18x^2+18x-56=0 | | 2x^2y^2-7xy-15=0 | | 6y^2-7y+2=0 | | -6x--12=72 | | 9c+2=2-4c | | 9y=2(7y-5) | | 9y=2(7-5) | | 6y+12c=18 |